Prediction of in vitro and in vivo DM digestibility of different forages using rumen liquor and dung liquor as inoculum - Kumar, Shiv; Gupta, P C (The Indian Journal of Animal Sciences, 2012)
Samples (24) of known digestibility were taken for in vitro dry-matter digestibility using rumen liquor (RL) and dung liquor (DL) as source of inoculum. The in vitro dry-matter digestibility coefficients obtained by using RL and DL were positively correlated (P<0.05) with in vivo dry matter digestibility and among themselves. The relationship was expressed in the form of regression equation. The predicted dry matter digestibility by the prediction equation developed from both the sources of inoculum were quite close to the actual known in vivo DM digestibility. The in vivo DM digestibility were 57.29, 57.42 and 58.71% for non-legumes, legumes and mixed forages and predicted digestibility were 57.58, 56.96 and 58.52 % (predicted from equation 2) and 57.93, 57.72 and 58.18 % (predicted from equation 3).